An Empirical Investigation of the Ohlson Model–A Panel Cointegration Approach - Shih-Cheng Lee; Jiun-Lin Chen; Ming-Shann Tsa (Australasian Accounting, Business and Finance Journal, 2014)
This paper uses a panel cointegration method to test the Ohlson (1995) model. Sample firms are selected from US listed companies during the period from 1986 to 2004. The analysis is focussed on whether the fundamental value of corporations cointegrates with market value. The results support the hypothesis of cointegration that a long-run equilibrium relationship exists between a corporation’s fundamental value and market value. Subsequently, this paper evaluates the predictive power of the Ohlson model for future market value assessment. Since the Ohlson model is built upon the dividend discount model, this paper also examines the validity and the predictive power of the dividend discount model as a basis for comparison. The results show that the Ohlson model can forecast future stock price movements much more accurately in any predicted horizon.
Keywords: Ohlson model; dividend discount model; panel cointegration; Theil’s U statistic